2019
DOI: 10.1680/jgeot.17.t.044
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated hydraulic properties of vegetated soil under single and mixed planting conditions

Abstract: Unsaturated hydraulic properties of vegetated soil under single and mixed planting conditions Ni, J. J .; Leung, Anthony; Ng, C. W. W. Published in: Géotechnique DOI:10.1680/jgeot.17.t.044 Publication date: 2018 Document Version Peer reviewed version Link to publication in Discovery Research Portal Citation for published version (APA):Ni, J. J. ., Leung, A., & Ng, C. W. W. (2018). Unsaturated hydraulic properties of vegetated soil under single and mixed planting conditions. Géotechnique. https://doi.org/10.168… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The denser vegetation established at the toe of the monitored hillslope may have been due to more optimal conditions for plant growth in terms of soil water and nutrients availability, which tend to accumulate naturally downslope (e.g., [34]). It is worth noting that willow-vegetated soil exhibited higher θv levels than fallow soil during part of the monitoring period (Figures 2 and 3), suggesting that vegetated soil can have a higher water retention capacity than fallow soil (e.g., [21]). The latter may be associated with the lower bulk density (i.e., higher soil porosity and thus, volume to be filled with water [18]) observed in the willowvegetated transect, which in turn is influenced by the plant cover through the incorporation of organic matter into the soil [41] and through soil structural changes related to the root system [5,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The denser vegetation established at the toe of the monitored hillslope may have been due to more optimal conditions for plant growth in terms of soil water and nutrients availability, which tend to accumulate naturally downslope (e.g., [34]). It is worth noting that willow-vegetated soil exhibited higher θv levels than fallow soil during part of the monitoring period (Figures 2 and 3), suggesting that vegetated soil can have a higher water retention capacity than fallow soil (e.g., [21]). The latter may be associated with the lower bulk density (i.e., higher soil porosity and thus, volume to be filled with water [18]) observed in the willowvegetated transect, which in turn is influenced by the plant cover through the incorporation of organic matter into the soil [41] and through soil structural changes related to the root system [5,42].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the relationship between the soil moisture and matric suction established through the soil water characteristic curve (SWCC; [19]) provides a good basis to bridge soil hydrology and mechanics [18]. Still, SWCCs for plant-soil composites either are difficult to obtain or have not yet been reported accurately (e.g., [3,20,21]). Moreover, only a handful of field studies have been undertaken to collect field-based knowledge on how vegetation influences the distribution of soil moisture and matric suction within hillslopes (e.g., [3,16,22]).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this may be blockage of pores due to root permeation. However, some other studies [21][22][23] show that water-holding capacity decreases due to the decay and shrinkage of roots. Accurate measurements of moisture content in GI is vital to analyse evapotranspiration, groundwater recharge and cloud formation (i.e., soil-plant-atmosphere interaction [24,25])…”
Section: Introductionmentioning
confidence: 95%
“…Chui et al [6] analyzed two geological cases in Singapore, and they used the ordinary leather method and the simple Kriging method (SK) to estimate the spatial variability of the air-entry value of the soil. Ni et al [7] used the instantaneous profile method to quantify the influence of plant roots on the air-entry value, and they found that the presence of roots significantly increased the airentry value of silt. Under mixed planting with rotted roots, the vegetation soil showed a significant decrease in the air-entry value.…”
Section: Introductionmentioning
confidence: 99%